Neural correlates of a mindfulness-based intervention in anorexia nervosa. Issue 1 (2nd January 2023) - Noda, Tomomi; Isobe, Masanori; Mishima, Ryo; Tose, Keima; Kawabata, Michiko; Aso, Toshihiko; Tei, Shisei; Noma, Shun'ichi; Murai, Toshiya
Summary: We examined the neural underpinnings of the effects of mindfulness on anxiety in anorexia nervosa using functional magnetic resonance imaging in 21 anorexia patients. We used a functional magnetic resonance imaging task designed to induce weight-related anxiety and asked participants to regulate their anxiety either using or not using an acceptance strategy. Our results showed reduced activity in the amygdala, anterior cingulate cortex, putamen, caudate, orbital gyrus, middle frontal gyrus, posterior cingulate cortex and precuneus following a mindfulness-based intervention. The present study provides new insight regarding the neural mechanisms underlying the effect of mindfulness-based intervention in ameliorating anorexia nervosa.